Family Law in Islamic and Secular Traditions: A Balanced Comparative Study on Gender Equity and Legal Reform - Zahraa Mahdi Dahash (Qiyam Islamic Studies Center Foundation, 2025)
Gender equity within family-law adjudication remains a global challenge as legal systems reconcile religious authority with constitutional equality and human-rights obligations. This study aims to compares eight jurisdictions to identify how doctrinal interpretation, procedural capacity, and enforcement credibility interact to deliver or impede gender-just rulings in marriage, divorce, maintenance, and succession cases. An explanatory-sequential mixed-methods design combined thematic exegesis of 112 statutes and 289 appellate judgments (2015–2025) with 48 semi-structured interviews, 36 hours of courtroom observation, and a coded administrative dataset of 2 430 family cases. Quantitative analyses employed mixed-effects logistic regression, difference-in-differences estimation, and fuzzy-set qualitative comparative analysis, while qualitative data were thematically mapped to statistical patterns. Maqāṣid-oriented reasoning increased the probability of an equitable ruling by 37 % and raised average monetary relief by 40 %. Reciprocal ʿiddah reforms boosted mean maintenance awards by up to 38 % and elevated compliance rates from 48 % to 85 %. Procedural access proved decisive: interpreter availability and legal-aid latency together explained 46 % of outcome variance, and equity climbed sharply once interpreter coverage exceeded 80 % and female judges comprised at least 40 % of benches. Jurisdictions aligning all three levers—doctrine, procedure, enforcement—achieved the highest and most durable equity scores. The findings demonstrate that gender-just family law is best secured through an integrated equity mechanism marrying purposive Islamic hermeneutics with robust procedural supports and credible sanctions. Future reforms should prioritize interpreter pools, gender-balanced judiciaries, and scalable enforcement tools to convert doctrinal potential into lived equality. These insights help policymakers design evidence-based, context-sensitive reforms worldwide.